Effects of Dietary Silica Nanoparticle on Growth Performance, Protein Digestibility, Hematology, Digestive Morphology, and Muscle Composition of Nile Tilapia, Oreochromis Niloticus - Bashar, Abul; Hasan, Neaz A.; Haque, Mohammad Mahfujul; Rohani, Md. Fazle; Hossain, Md. Sazzad (Frontiers in Marine Science, 2021)
The use of nanotechnology in food production systems is being investigated globally, though there is limited research on its effect on fish nutrition. Therefore, this study aimed to identify the effects of silica nanoparticles (NPs) on the nutrition and physiology of tilapia, Oreochromis niloticus. Four isonitrogenous diets (300 g/kg crude protein) with NPs (0, 1, 2, and 3 mg/kg diet) were fed to fish (6.52 ± 0.20 g) in a recirculatory aquaculture system for 56 days. Throughout the study period, the effects of silica NP on survival rate, blood cell count, hemoglobin (Hb) level, condition factor (CF), and final product composition (except lipid content) were insignificant. However, growth performance and feed efficiency increased with an increasing level of silica NP, up to 2 mg/kg, and then decreased. This increase was due to the highest apparent protein digestibility and dry matter digestibility when fish were fed silica NP at 2 mg/kg. However, fish at the early stage showed better performance in all dietary groups than in later. Blood glucose (BG) content and histology of the kidney revealed that fish were stressed when a 3 mg/kg silica NP was used and they adapted through excessive excretion via expanded glomeruli. Though no significant effect on villi length was observed, silica NP increased the surface area widening the villi of the gut along with the number of goblet cells in the intestine significantly, when supplemented at a level of 2 mg/kg. The bioaccumulation of silica shows that incorporating silica NP in the fish feed will not compromise human health safety upon consumption. Although silica NP at 1 mg/kg and 3 mg/kg yielded some improvements to growth and final product quality, a 2 mg/kg silica NP generated the best results in all measured parameters.